Clindamycin-Induced Esophageal Injury: Is It an Underdiagnosed Entity? - Bestari, Muhammad Begawan (Clin Med Insights Case Rep, 2019)
There are increased reports of pill-induced esophagitis in the past 2 decades, with almost 100 different substances identified as the cause for more than 700 cases, and the overall incidence is estimated to be 0.004% per year. Antibiotics are one of the major contributors for these cases, especially tetracycline and doxycycline; other major contributors are bisphosphonates, nonsteroidal anti-inflammatory drugs, and iron pills. Clindamycin is commonly prescribed by physicians, yet side effect in the form of esophagitis is uncommon and mostly documented in case report. It is possible that these cases are mostly unnoticed due to initial consideration of common and more serious problems. Thus, patients may be assumed to be having a severe episode of acid reflux, and it is not routinely reported or recognized. In this case series, we presented 8 patients with clindamycin-induced esophagitis. The initial presentation of all patients was odynophagia, which appeared within the first day of taking the antibiotic. All patients were subjected to endoscopic examination and ulcer was found in all cases, in the form of localized solitary or multiple ulcers with sharply defined borders. Patients were treated with proton pump inhibitor and sucralfate, and the symptoms subside within 1 week. Patient education regarding the proper way of ingesting drug seems to be the key factor in the prevention of pill-induced esophagitis. The prevention of esophagitis is even more important with antibiotics as adverse effect would decrease the patient compliance in completing the regimen and would ultimately increase antibiotic resistance.